Approximation by trigonometric polynomials in the variable exponent weighted Morrey spaces
In this paper we investigate the best approximation by trigonometric polynomials in the variable exponent weighted Morrey spaces M _p(·),λ(·)(I_0,w), where w is a weight function in the Muckenhoupt A_p(·)(I_0) class. We get a characterization of K-functionals in terms of the modulus of smoothness in the spaces M _p(·),λ(·)(I_0,w). Finally, we prove the direct and inverse theorems of approximation by trigonometric polynomials in the spaces M _p(·),λ(·)(I_0,w), the closure of the set of all trigonometric polynomials in M _p(·),λ(·)(I_0,w). , number=3, journal=Carpathian Mathematical Publications, author=Cakir, Z. and Aykol, C. and Guliyev, V.S. and Serbetci, A., year=2021, month=Dec., pages=750–763